Analyzing Students' Contextual Problem-Solving on the Pythagorean Theorem Based on Learning Styles - Amelia Rida Zahra Hardian Hardian; Tatag Yuli Eko Siswono; Novita Vindri Harini (MATHEdunesa, 2026)
This study aims to explore the problem-solving processes of students in solving contextual problems related to the Pythagorean Theorem based on their learning styles. This study uses a qualitative descriptive approach involving three students representing visual, auditory, and kinesthetic learning styles. Data were collected through written tests and semi-structured interviews, and analyzed through data reduction, data display, and conclusion drawing. The results show that students demonstrate different ways of thinking in constructing problem-solving processes. Visual learners tend to use diagrams and visual representations to organize information. Auditory learners demonstrate a sequential problem-solving process through verbal reasoning and internal dialogue. Meanwhile, kinesthetic learners engage with the problem through physical and spatial imagination using movement and gestures. Although some parts of the process are expressed through different forms, such as verbal explanation or mental reflection, the findings show that students construct understanding and connect mathematical concepts with contextual situations. These results emphasize that differences in learning styles are reflected in how students think, represent, and process problems